PENGURUSAN DAN PENGELOLAAN HARTA KEKAYAAN SUAMI ISTRI KE DALAM SUATU LEMBAGA “ TRUST” DAN AKIBAT HUKUMNYA TERHADAP HAK AHLI WARIS BERDASARKAN HUKUM WARIS PERDATA BARAT - Armey Haryssa (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
This thesis discusses theagreement on the management of the husband-wife’s assets under Trusts, as acknowledged in Anglo Saxon countries, in order to protect the family assets for future generations. The issues focus on how the enforcement of such an agreement is basedon Indonesia'slaws which, in general, do not acknowledge the trustsconcept (i.e., separation between legal ownership and beneficial ownership). In addition, the provisions under such agreement can potentially infringe the inheritance laws under the Indonesian Civil Code and in this case, whether the inheritance disposition will be subject to the inheritance laws or the said agreement. This thesis’ research methodology is legal normative. The research result has shown that the agreement on the establishment of a Trust for the purpose of managing the husband-wife’s assets cannot be made and enforced under Indonesia'slaws, rather it should be made and governed based on the foreign law where the Trust is established. However, such agreement will still be subject to the forced heirship laws under the Indonesian Civil Code (including the heir’s mandatory portion protected under the law or known as legitieme portie) and must be supported by a testament, being the stipulation acknowledged under the law to waive the applicability of the inheritance provisions under the law (to the extent permitted). Without a testament, the inheritance disposition will be determined by the law regardless of such agreement.  Considering that setting up a Trust in other countries will be more beneficial to those assets located outside Indonesia, the Indonesian Civil Code also acknowledges several institutions having characteristics similar to Trust which may be used as mechanism for managing the inheritance estate (excluding legitieme portie) so as to protect those portion of estate for future generations.